Whole blood FPR1 mRNA expression predicts both non‐small cell and small cell lung cancer. Issue 11 (30th January 2018) - Morris, Scott; Vachani, Anil; Pass, Harvey I.; Rom, William N.; Ryden, Kirk; Weiss, Glen J.; Hogarth, D. K.; Runger, George; Richards, Donald; Shelton, Troy; Mallery, David W.
Abstract : While long‐term survival rates for early‐stage lung cancer are high, most cases are diagnosed in later stages that can negatively impact survival rates. We aim to design a simple, single biomarker blood test for early‐stage lung cancer that is robust to preclinical variables and can be readily implemented in the clinic. Whole blood was collected in PAXgene tubes from a training set of 29 patients, and a validation set of 260 patients, of which samples from 58 patients were prospectively collected in a clinical trial specifically for our study. After RNA was extracted, the expressions of FPR1 and a reference gene were quantified by an automated one‐step Taqman RT‐PCR assay. Elevated levels of FPR1 mRNA in whole blood predicted lung cancer status with a sensitivity of 55% and a specificity of 87% on all validation specimens. The prospectively collected specimens had a significantly higher 68% sensitivity and 89% specificity. Results from patients with benign nodules were similar to healthy volunteers. No meaningful correlation was present between our test results and any clinical characteristic other than lung cancer diagnosis. FPR1 mRNA levels in whole blood can predict the presence of lung cancer. Using this as a reflex test for positive lung cancer screening computed tomography scans has the potential to increase the positive predictive value. This marker can be easily measured in an automated process utilizing off‐the‐shelf equipment and reagents. Further work is justified to explain the source of this biomarker. Abstract : What's new? There have been several lung cancer screening trials evaluating the potential benefit of imaging for improving survival outcomes in lung cancer patients. While low‐dose computed tomography (CT) screening reduces mortality, it yields a 96.4% false‐positive rate. A potential strategy to improve screening may be the identification of additional tools that improve identification of false positives. Using prospectively collected whole blood samples, here the authors show that elevated FPR1 mRNA expression has a 68% sensitivity and 89% specificity. This single biomarker blood test, which can be readily implemented in the clinic, may increase the positive predictive value of detecting lung cancer.